2016
DOI: 10.1162/evco_a_00143
|View full text |Cite
|
Sign up to set email alerts
|

Evolving a Behavioral Repertoire for a Walking Robot

Abstract: Numerous algorithms have been proposed to allow legged robots to learn to walk. However, most of these algorithms are devised to learn walking in a straight line, which is not sufficient to accomplish any real-world mission. Here we introduce the Transferability-based Behavioral Repertoire Evolution algorithm (TBR-Evolution), a novel evolutionary algorithm that simultaneously discovers several hundreds of simple walking controllers, one for each possible direction. By taking advantage of solutions that are usu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 53 publications
1
88
0
Order By: Relevance
“…Recent work in Evolutionary Robotics (ER) (Doncieux et al, 2015) has provided increasing empirical evidence that maintaining diversity in genotypes (robot controller encodings) and phenotypes (robot behaviors) improves the quality (task performance) of evolved behaviors in a range of tasks (Mouret and Doncieux, 2012;Cully et al, 2015;Cully and Mouret, 2016;Gomes et al, 2016).…”
Section: Behavioral and Genotypic Diversity Maintenancementioning
confidence: 99%
See 3 more Smart Citations
“…Recent work in Evolutionary Robotics (ER) (Doncieux et al, 2015) has provided increasing empirical evidence that maintaining diversity in genotypes (robot controller encodings) and phenotypes (robot behaviors) improves the quality (task performance) of evolved behaviors in a range of tasks (Mouret and Doncieux, 2012;Cully et al, 2015;Cully and Mouret, 2016;Gomes et al, 2016).…”
Section: Behavioral and Genotypic Diversity Maintenancementioning
confidence: 99%
“…Recent work in Evolutionary Robotics (ER) (Doncieux et al, 2015) has provided increasing empirical evidence that maintaining diversity in phenotypes (robot behaviors) improves the quality (task performance) of evolved behaviors (Mouret and Doncieux, 2012;Cully et al, 2015;Cully and Mouret, 2016;Gomes et al, 2016). Specifically, replacing objective search with the search for behavioral diversity in controller evolution (Moriguchi and Honiden, 2010;Mouret and Doncieux, 2012;Lehman et al, 2013;Gomes et al, 2015) has been demonstrated to boost the quality of evolved behaviors across a range of simulated (Lehman and Stanley, 2011a;Mouret and Doncieux, 2012;Gomes et al, 2016) and physical (Cully et al, 2015;Cully and Mouret, 2016) ER tasks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The seminal work by Sims (1994) remains an exemplar to the present day. Subsequent research has made incremental steps from this point, including demonstrating realistic co-adapted behaviours using just general purpose neurons (Miconi and Channon, 2006), making use of a human-specified syllabus of reactive locomotion-based tasks (Lessin et al, 2013) and using Novely Search (Lehman and Stanley, 2008) to evolve a range of gaits for a fixed morphology robot (Cully and Mouret, 2015), but continues to focus primarily on locomotion alone, leaving more complex behaviours aside.…”
Section: The Dimensionality Of Virtual Environmentsmentioning
confidence: 99%